Fastening technology in construction for sustainability through building information modeling - Mohandes, Saeed Reza (2014)
One of the most the most vital aspects of construction industry which needs to be taken into account is sustainability development. This issue has been categorized into different subdivisions such as thermal properties, sound insulation, environmental impacts and flexibility. One critical element of the buildings playing a pivotal factor in order to meet the resident’s needs on the interior space is partition wall. Although some research has been carried out on the subject of sustainability in different aspects of partition walls such as embodied energy or thermal properties, there has not been any research carried out exploiting BIM (building information modeling) as a tool in order to simulate work process, calculate time and take-off quantities pertaining to this crucial element on the interior space of the buildings. Gaining innumerable benefits regarding the usage of BIM have been overlooked over the past researches conducted on the field of partition walls. As a result, this research has presented a new framework of exploiting BIM software in doing so. The main goal of this research is to propose a new type of partition wall and its fasteners with the aim of shortening the installation process, materials needed and enhancing the functionality on the interior space of the buildings. The objectives of this study are: 1) To calculate time and quantity take-off pertaining to the existing partition walls and their fasteners, 2) To propose a new partition wall with its fasteners and 3) To examine the effectiveness of new partition wall in terms of time, material saving and functionality. The scope of presented work is limited to the connections between the partition walls to the exterior walls and to the columns. To achieve the mentioned objectives, a case study has been chosen. The used methodology has comprised the simulation of work process regarding each partition wall using Revit Architecture and Autodesk Inventor and calculation the quantity and time required to install each employing Naviswork Manage 2014. The results have shown that the proposed partition wall would be by far more effective to be used on the interior space of the buildings in comparison with the other results